2019
DOI: 10.1073/pnas.1901039116
|View full text |Cite
|
Sign up to set email alerts
|

SIP/CacyBP promotes autophagy by regulating levels of BRUCE/Apollon, which stimulates LC3-I degradation

Abstract: BRUCE/Apollon is a membrane-associated inhibitor of apoptosis protein that is essential for viability and has ubiquitin-conjugating activity. On initiation of apoptosis, the ubiquitin ligase Nrdp1/RNF41 promotes proteasomal degradation of BRUCE. Here we demonstrate that BRUCE together with the proteasome activator PA28γ causes proteasomal degradation of LC3-I and thus inhibits autophagy. LC3-I on the phagophore membrane is conjugated to phosphatidylethanolamine to form LC3-II, which is required for the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
4
41
0
Order By: Relevance
“…In any event, the mechanism involving LC3B ubiquitination and degradation revealed by our study is consistent with the activity of BIRC6 as an E2/E3 enzyme. While our manuscript was in preparation, another study showed that BIRC6 targeted LC3B-I for proteasomal degradation, and that BIRC6 itself was subject to proteasomal degradation promoted by the ubiquitin ligase RNF41/NRDP1 (neuregulin receptor degradation protein-1) and inhibited by CACYBP/SIP (calcyclin-binding protein/siah-1 interacting protein) (Jiang et al, 2019). Taken together, these findings reveal the existence of a complex regulatory network for the control of LC3B levels.…”
Section: Discussionmentioning
confidence: 99%
“…In any event, the mechanism involving LC3B ubiquitination and degradation revealed by our study is consistent with the activity of BIRC6 as an E2/E3 enzyme. While our manuscript was in preparation, another study showed that BIRC6 targeted LC3B-I for proteasomal degradation, and that BIRC6 itself was subject to proteasomal degradation promoted by the ubiquitin ligase RNF41/NRDP1 (neuregulin receptor degradation protein-1) and inhibited by CACYBP/SIP (calcyclin-binding protein/siah-1 interacting protein) (Jiang et al, 2019). Taken together, these findings reveal the existence of a complex regulatory network for the control of LC3B levels.…”
Section: Discussionmentioning
confidence: 99%
“…These results thus demonstrated that USP10 depletion reduced the levels of endogenous LC3B, an effect that was opposite to that caused by depletion of the ubiquitinating enzymes UBA6 or BIRC6 (11,12). LC3B can be turned over by both lysosomal (16) and proteasomal degradation (11)(12)(13). To examine which pathway was responsible for the reduced levels of LC3B in USP10deficient cells, we tested the effect of specific inhibitors.…”
Section: Resultsmentioning
confidence: 94%
“…We and others found that LC3B is monoubiquitinated by the concerted action of the UBA6 E1 ubiquitin (Ub)-activating enzyme and the BIRC6 hybrid E2 ubiquitin-conjugating enzyme/E3 Ub ligase ( 11 , 12 ), and polyubiquitinated by the von Hippel–Lindau (VHL) tumor suppressor E3 Ub ligase ( 13 ). Both monoubiquitination and polyubiquitination lead to proteasomal degradation of LC3B, with consequent decrease in autophagic activity ( 11 , 12 , 13 ). In general, protein ubiquitination is reversed by Ub removal catalyzed by a family of isopeptidases known as deubiquitinating enzymes (DUBs) ( 14 ).…”
mentioning
confidence: 99%
“…We also observed the synergetic protective effect of baicalein and MARCH5 on H 2 O 2 induced cardiotoxicity (Figure C–E). Most recent studies have revealed that ubiquitination can promote apoptosis, we then tested the modification of MARCH5 by ubiquitin. As shown in Figure B, the mount of ubiquitin‐MARCH5 noticeable increased compared with control under oxidative stress.…”
Section: Resultsmentioning
confidence: 99%